Design of a VLAN-Based Wireless Network Based on IEEE 802.11 Employing OSPF (Open Shortes Path First) at PT. Sepatu Bata (Tbk) - Rino Subekti; RR Aryanti Kristantini; Rizaldy Khair; Iswandi Idris (The IJICS (International Journal of Informatics and Computer Science), 2021)
Wireless network is a technology that uses two devices to exchange data without the need for cables to transmit data, so this wireless network technology very popular nowadays both in personal use and in industrial use. This design is based on the increasing demand for data and technology. Therefore PT. Sepatu Bata (Tbk), requires the development of a computer network that can be developed easily and flexibly. Design and design of VLAN network technology using OSPF Routing Protocol at PT. Bata TBK shoes use a packet tracer. One alternative that can be used is an attempt to use Virtual Local Zone Network technology (VLAN), with the hope of sharing better results than LAN. VLAN a logical function of the switch, which is a special function configured for use software features. This function will divide the network into virtual networks that physically still connected to the same switch. With this function, computer technology can be made without depending on physical location, but based on needs and uses. VLANs can be used make flexible network arrangements with ministry segmentation match industry and can only broadcast to certain groups without relying on workstation position, besides the purpose of this study is to design a new network that more optimally by using a VLAN network with the OSPF routing protocol